Penatalaksanaan Fisioterapi Pada Kondisi Sinusitis Maksilaris Bilateral dengan Modalitas Ultrasound dan Face Massage (Sinus Acupressure Point) di Rsud Kajen Kabupaten Pekalongan - irine almeera; Nur Faizah (Universitas Muhadi Setiabudi, 2023)
ABSTRACT Sinusitis is an inflammation of the nose and paranasal sinuses characterized. The purpose of riset is to understand the implementation of physiotherapy in reducing pain, in the sinusitis maksilaris condition with ultrasound modility and face massage with tecnique sinus acupressure point. This research was carried out in Kajen District Hospital Pekalongan with descriptive analytic methods. Once done six times therapy, results obtained the presence of pain reduction. T1 to T6 obtained the following results: T1 tenderness 6 and silent pain 6, on T2 tenderness 6 and silent pain 6, T3 tenderness 5 and silent pain 6, T4 silent pain 5 and silent pain 5, T5 result of tenderness 5 and silent pain 4 and T6 tenderness 3 whereas the rest pain becomes 2. Interventions physiotherapy using ultrasound modality and face massage in tecnique sinus acupressure point, can help reduce the pain of sinusitis condition.